Analisis Pembuatan Media Visual untuk Pembelajaran Mufradat oleh Mahasiswa Magister Pendidikan Bahasa Arab UIN Sunan Kalijaga Yogyakarta - Hidayati, Nur Laili (Study Program of Arabic Language Teaching, 2021)
This research was conducted based on the importance of the function of learning media in the success of the teaching process. conducted this research based on the importance of the function of learning media in the success of the teaching process. The research is intended to determine the ability of students to produce effective learning media to support the achievement of learning objectives. This research is descriptive research. The data studied are the results of learning media in visual form in the Arabic language learning media course. The data were analyzed according to the criteria of effective learning media, among others in terms of 1) the accuracy of the media with teaching objectives; 2) support for the content of learning materials; 3) easy access to media; 4) the skills of the teacher in using it, and 5) according to the child's level of thinking. From the data analysis, several conclusions were made that 1) Media can be used for several competencies at once in one material theme. Thus, it will help teachers in the effectiveness of the allocation of learning time; 2) Several media such as spinner mufradat can be used simultaneously in taking the value of learning evaluation; 3) Making visual media can help teachers as facilitators so that teachers are more conceptualized in implementing learning. The results of making visual media by students are classified as successful because students can produce media that are effective in time allocation, easy to operate, and attractive in appearance.